The Effects of European Economic Integration on the Profitability of Industries - Hakura, Dalia (IMF Working Papers; Working Paper ;, 1998)
This paper examines the effects of intensified international competition on industry profits in six European Union (EU) countries. The paper uses two methods to estimate industry profits. The traditional method uses accounting data to obtain a measure of gross price-average cost margins. The second method directly estimates markups of price over marginal cost using new empirical techniques. Import competition is found to have disciplined market power, regardless of the method used to estimate industry profits. From the analysis of the markups, there is evidence that this is due mainly to intra-EU import competition. The evidence for export discipline is much weaker.